Singapore's success : - Ghesquiere, Henri C. (Thomson, 2007)
This monograph seeks the key to good economic policy by explaining Singapore's remarkably rapid development - the world's fastest-growing economy between 1960 and 2000 - and asks whether the city-state's success can be translated to other countries. Engineering prosperity is at the heart of Singapore. The book demonstrates how exceptional cohesion amongst economic outcomes, policies, institutions, values and leadership over a long period accounts for the impressive results obtained. The author is careful not to present Singapore as a model to be copied uncritically in its specifics but as a case history that illustrates general principles which other countries might wish to apply to their particular circumstances.